Sequential Control over Thiol Click Chemistry by a Reversibly Photoactivated Thiol Mechanism of Spirothiopyran. (12th November 2014) - Liu, Zhenzhen; Liu, Tao; Lin, Qiuning; Bao, Chunyan; Zhu, Linyong
Abstract: A novel photocontrolled thiol click chemistry based on spirothiopyran and maleimide is reported. Upon irradiation with λ=365 nm light, the spirothiopyran can isomerize to the open merocyanine form, a thiophenolate group, which can rapidly react with maleimide. The unreacted MC will readily isomerize back to the starting spirothiopyran, which can be repeatedly photoactivated as needed. Thus, this reversible photoactivated thiol confers spatiotemporal sequential control on the thiol–maleimide reaction using only one type of photochemical reaction. Polymer post‐functionalization and hydrogel building with subsequent multipatterning using different maleimide molecules in a temporal sequential manner indicate that this photocontrolled Michael addition reaction can modulate the specific chemical events in a sequence. Abstract : Bei Bedarf : Die reversible photoaktivierte Thiolbildung durch ein Spirothiopyran ermöglicht eine räumlich kontrollierte Thiol‐Klick‐Reaktion. Eine spezifische Abfolge von Ereignissen lässt sich leicht mithilfe einer einzigen Art von photochemischer Thiol‐Klick‐Reaktion aufbauen.